Salvianolic acid B inhibits autophagy and activation of hepatic stellate cells induced by TGF-β1 by downregulating the MAPK pathway - Na Jiang; Jing Zhang; Jian Ping; Jian Ping; Lieming Xu; Lieming Xu; Lieming Xu; Lieming Xu (Frontiers Media S.A., 2022)
In liver fibrosis, transforming growth factor-β1 (TGF-β1) can stimulate autophagy and activation of hepatic stellate cells (HSCs). Autophagy, playing a crucial role in HSCs activation, is related to liver fibrosis. Increasing evidence have suggested that antifibrosis effects of salvianolic acid B (Sal B) and their mechanisms of action, however, remain unclear. The aim of the article is to understand the role of Sal B in HSCs autophagy in liver fibrosis. Herein, we demonstrated that inducing TGF-β1 led to dramatic increase in autophagosome formation and autophagic flux in JS1 and LX2, which was mediated through the ERK, JNK, and p38 MAPK cascades. TGF-β1 significantly increased the protein of autophagy and liver fibrosis, including LC3BⅡ, ATG5, α-SMA, and Col.I; Sal B inhibits JS1 autophagy and activation by inhibiting the formation of autophagosomes and autophagic flux. Sal B significantly decreased the LC3BⅡ, ATG5, α-SMA, and Col.I protein expressions; pretreatment with autophagy inhibitors, chloroquine (CQ) and 3-methyladenine (3-MA) or silencing ATG7 further increase these reductions. However, pretreatment with autophagy agonist, rapamycin (Rapa), or overexpressed ATG5 attenuated this decrease. To further assess the importance of this mechanism, the antibody chip was used to detect the change of phosphorylation protein expression of the MAPK signaling pathway after treating JS1 with Sal B. Eleven differentially expressed proteins were verified. Sal B inhibits activation and autophagy of JS1 induced by TGF-β1 through downregulating the ERK, p38, and JNK signaling pathways, as demonstrated by downregulating p-ERK, p-JNK, and p-p38 MAPK protein expressions. In conclusion, Sal B inhibits autophagy and activation induced by TGF-β1 of HSCs possibly by downregulating the MAPK pathway.